Genitourinary Tuberculosis: An Atypical Clinical Presentation - Pei Shan Lim; Ixora Kamisan Atan; Aruku Naidu (Case Reports in Obstetrics and Gynecology)
Genitourinary tuberculosis is one of the common forms of extrapulmonary tuberculosis. We report a case of atypical genitourinary tuberculosis: massive uterovaginal prolapse with cervical lesion mimicking cervical carcinoma. This particular case highlights the problem of healthcare in most of the developing countries. Lack of patient education, awareness, and access to a healthcare system resulted in a complicated situation. In an endemic area or in an immunocompromised individual, a higher index of suspicion would allow early recognition and treatment institution to minimise its late consequences as well as spreading of the disease. Though anti-TB is the mainstay of treatment, surgical intervention might be needed in selected cases.